Reduced Auditory Mismatch Negativity Reflects Impaired Deviance Detection in Schizophrenia - Koshiyama, Daisuke; Kirihara, Kenji; Tada, Mariko; Nagai, Tatsuya; Fujioka, Mao; Usui, Kaori; Araki, Tsuyoshi; Kasai, Kiyoto (Schizophrenia bulletin, 2020)
The auditory mismatch negativity (MMN) is a translatable electroencephalographic biomarker automatically evoked in response to unattended sounds that is robustly associated with cognitive and psychosocial disability in patients with schizophrenia. Although recent animal studies have tried to clarify the neural substrates of the MMN, the nature of schizophrenia-related deficits is unknown. In this study, we applied a novel paradigm developed from translational animal model studies to carefully deconstruct the constituent neurophysiological processes underlying MMN generation. Patients with schizophrenia (N = 25) and healthy comparison subjects (HCS; N = 27) underwent MMN testing using both a conventional auditory oddball paradigm and a “many-standards paradigm” that was specifically developed to deconstruct the subcomponent adaptation and deviance detection processes that are presumed to underlie the MMN. Using a conventional oddball paradigm, patients with schizophrenia exhibited large effect size deficits of both duration and frequency MMN, consistent with many previous studies. Furthermore, patients with schizophrenia showed selective impairments in deviance detection but no impairment in adaptation to repeated tones. These findings support the use of the many-standards paradigm for deconstructing the constituent processes underlying the MMN, with implications for the use of these translational measures to accelerate the development of new treatments that target perceptual and cognitive impairments in schizophrenia and related disorders.